2023
DOI: 10.3390/microorganisms11040818
|View full text |Cite
|
Sign up to set email alerts
|

Candida spp. DNA Extraction in the Age of Molecular Diagnosis

Abstract: The standard procedure for the detection of candidemia is blood culture, a method that might require 3–5 days for a positive result. Compared with culturing, molecular diagnosis techniques can provide faster diagnosis. The current paper aimed to present the main strengths and constraints of current molecular techniques for Candida spp. DNA extraction, analyzing their efficiency from a time, price, and ease of usage point of view. A comprehensive search was conducted using the PubMed NIH database for peer-revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Over the past few decades, accumulated experience with manual (including in-house) or automated DNA extraction protocols for Candida (or other yeast) species has shown that the yield of DNA extracted from whole blood samples can be variable (limit of detection ranges from 10 0 to 10 6 CFU/mL for manual protocols and from 10 1 to 10 6 CFU/mL for automated protocols) [ 11 ]. This variability is imputable as to whether pretreatment (mechanical, enzymatic, chemical, physical, or thermal) or no treatment was applied to the sample before proceeding with DNA isolation from Candida cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, accumulated experience with manual (including in-house) or automated DNA extraction protocols for Candida (or other yeast) species has shown that the yield of DNA extracted from whole blood samples can be variable (limit of detection ranges from 10 0 to 10 6 CFU/mL for manual protocols and from 10 1 to 10 6 CFU/mL for automated protocols) [ 11 ]. This variability is imputable as to whether pretreatment (mechanical, enzymatic, chemical, physical, or thermal) or no treatment was applied to the sample before proceeding with DNA isolation from Candida cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, accumulated experience with manual (including in-house) or automated DNA extraction protocols for Candida (or other yeast) species has shown that the yield of DNA extracted from whole blood samples can be variable (limit of detection ranges from 10 0 to 10 6 CFU/mL for manual protocols and from 10 1 to 10 6 CFU/mL for automated protocols) [ 11 ]. This variability is imputable as to whether pretreatment (mechanical, enzymatic, chemical, physical, or thermal) or no treatment was applied to the sample before proceeding with DNA isolation from Candida cells [ 11 ]. Very recently, Menu et al [ 10 ] used human blood samples artificially spiked with the Candida species ( C. albicans , C. glabrata , C. parapsilosis , C. tropicalis , and C. krusei , for which inoculum sizes ranged from 0 to 10 8 CFU/mL) to evaluate the efficiency of 11 automated DNA extraction protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation